O papel da Universidade Federal de Sergipe no sistema local de inovação - Santos, Clézia de Souza (2012)
The cooperation between names and network installation industry has marked the innovation process worldwide. Founded on the ideas of Schumpeter, neoschumpeterianos contributed to the formation of an instrumental inspired evolutionary Innovation Systems (IS). In this system the universities play a key role in the innovation process and the process of regional and local development, making it necessary for these institutions, the establishment of links with the market and society in general. This research aimed to examine the role of the Federal University of Sergipe (UFS) as part of the Innovation System of the State of Sergipe. The research strategy adopted was case study, having used the following data sources: the Directory of Research Groups CNPq; GeoCapes base; System Control Covenants of Program Coordination, Projects and Covenants (Copec) of Federal University of Sergipe, in addition to interviews with various agencies that make up the innovation system state. As a result, it is concluded that the UFS has a low interaction with the organs members of local innovation system. In cases where there is interaction with the productive sector, research, mostly refer to large area of knowledge of agricultural sciences and engineering.